Transpapillary Retrieval of a Proximally Migrated Stent Using a Three-prong Polyp Retrieval Device in a 2-years-old Girl - Goetz, M.; Walther, U.; Malek, N.; Fuchs, J.; Königsrainer, A.; Kratt, T. (Zeitschrift für Gastroenterologie, 2014)
Endoscopic retrieval of proximally migrated biliary stents is sometimes challenging. We report on the successful use of a three-prong colon polyp retrieval device in a two year old child.
Keywords: ERCP; Kind; Dislokation Gallengangsprothese